Formación previa al servicio docente en la provincia de Pichincha. - Almagro Calapiña, Víctor Marcelo (2018)
The educational system in Ecuador tends to generate gradual changes in the structure of this, which generates a satisfaction of the educational service that fulfills, and this is projected to satisfy the social, cultural academic needs in the daily exchange of teachers and students, for this reason The objective of this research was to diagnose the current situation on teacher training in the province of Pichincha, establishing bibliographical information to support the research generating a methodological procedure for the collection of data that provide starting points for situational diagnosis in Which is immersed the educator as a professional who performs actions for the good of other beings that exist to the education of the Ecuadorian system. For this reason, it has been necessary to present three specific objectives such as: to investigate bibliographical sources regarding the training of teachers within the educational context, to design the methodological procedure of the research for the collection of statistical data and to analyze the results of Data obtained for the elaboration of conclusions and recommendations with respect to the work investigated. The methodologies used were descriptive, bibliographic, qualitative and quantitative for the development of this investigative report. While the technique and research instrument was the survey, and a questionnaire addressed to the teachers of said place already mentioned. The impact is social and economic, since in talking about training, we are emphasizing the quality of life that has the professional and each member of his family, also allowing the educator can give an example in a society that usually works for good human relationships and the interests of people. Turning them to these professionals in the main beneficiaries and therefore to their student in charge, since a teacher prepared just will focus more on the preparation of their students.